Analysing the variation in farmers' perceptions of climate change impacts on crop production and adaptation measures across the Ganges' Tidal Floodplain in Bangladesh. Issue 8 (3rd August 2022) - Khan, Rafid Mahmud; Zulfiqar, Farhad; Datta, Avishek; Kuwornu, John K. M.; Shrestha, Sangam
ABSTRACT: Bangladesh is highly vulnerable to climate change (CC) and consequent agricultural productivity repercussions. This study aimed at exploring the difference in farmers' perceptions of CC impacts on crop production and variation in adaptation measures across the Ganges' Tidal Floodplain (GTF) region. To unlock the local level context-specific nature of adaptation, the study area covered two distinct zones of the GTF: interior zone, surrounded by the Sundarbans mangrove forest, and exterior zone being more exposed to the Bay of Bengal. An analysis of the differences in empirical climate parameter trends and farmers' adaptations to adjust to these changes in the two sample study areas (one from each zone) was conducted. In the exterior zone (Patuakhali), delayed monsoon and increasing intensity of post-monsoon rainfall coupled with poor water drainage resulted in delayed winter vegetable production and late harvest of rainy season rice ( aman ), eventually leading to a loss of winter rice season ( boro ). Rainfall in the interior zone (Satkhira) was found erratic and unevenly distributed causing unexpected loss of harvest. Farmers in both areas reported a high impact of CC on crop production. Farmers reported optimisation of fertiliser and pesticide use and planting date adjustment as the most practiced adaptations in both areas. Other preferred adaptation options were rice-fish farming in Satkhira and growing of high-value cash crops in Patuakhali. In terms of weighted average index scoring, Satkhira farmers on average had medium adaptation scores, while most of Patuakhali farmers had medium to low adaptation scores. Living in the same agroecological zone, the difference in farmers' perceptions, climate variability, and adaptation practices call for context- and location-specific adaptation planning and policy.